Using DNA-Stable Isotope Probing to Identify MTBE- and TBA-Degrading Microorganisms in Contaminated Groundwater - Key, Katherine C. (Ground Water Monit Remediat, 2013)
Although the anaerobic biodegradation of methyl tert-butyl ether (MTBE) and tert-butyl alcohol (TBA) has been documented in the laboratory and the field, knowledge of the microorganisms and mechanisms involved is still lacking. In this study, DNA-stable isotope probing (SIP) was used to identify microorganisms involved in anaerobic fuel oxygenate biodegradation in a sulfate-reducing MTBE and TBA plume. Microorganisms were collected in the field using Bio-Sep® beads amended with (13)C(5)-MTBE, (13)C(1)-MTBE (only methoxy carbon labeled), or(13)C(4)-TBA. (13)C-DNA and (12)C-DNA extracted from the Bio-Sep beads were cloned and 16S rRNA gene sequences were used to identify the indigenous microorganisms involved in degrading the methoxy group of MTBE and the tert-butyl group of MTBE and TBA. Results indicated that microorganisms were actively degrading (13)C-labeled MTBE and TBA in situ and the (13)C was incorporated into their DNA. Several sequences related to known MTBE- and TBA-degraders in the Burkholderiales and the Sphingomonadales orders were detected in all three(13)C clone libraries and were likely to be primary degraders at the site. Sequences related to sulfate-reducing bacteria and iron-reducers, such as Geobacter and Geothrix, were only detected in the clone libraries where MTBE and TBA were fully labeled with (13)C, suggesting that they were involved in processing carbon from the tert-butyl group. Sequences similar to the Pseudomonas genus predominated in the clone library where only the methoxy carbon of MTBE was labeled with (13)C. It is likely that members of this genus were secondary degraders cross-feeding on (13)C-labeled metabolites such as acetate.